Opioid Treatment Programs, Telemedicine and Covid-19: A Scoping Review. Issue 1 (December 2022) - Chan, Brian; Bougatsos, Christina; Priest, Kelsey C.; McCarty, Dennis; Grusing, Sara; Chou, Roger
Background : Methadone and buprenorphine are effective medications for opioid use disorder (MOUD) that are highly regulated in the United States. The on-going opioid crisis, and more recently COVID-19, has prompted reconsideration of these restrictions in order to sustain and improve treatment access, with renewed interest in telemedicine. We reviewed the evidence on use of telemedicine interventions and applicability to MOUD policy changes in the post-COVID-19 treatment landscape. Methods: Ovid MEDLINE and the Cochrane Database of Systematic Reviews databases were searched from inception to April 2021 and reference lists were reviewed to identify additional studies. Studies were eligible if they examined telemedicine interventions and reported outcomes (e.g. treatment initiation, retention in care). Randomized trials and controlled observational studies were prioritized; other studies were included when stronger evidence was unavailable. One investigator abstracted key information and a second investigator verified data. We described the results qualitatively. Results: We identified nine studies: three controlled trials (two randomized), and six observational studies. Three studies evaluated patients treated with methadone and six studies with buprenorphine, including one study of pregnant women with OUD. All studies showed telemedicine approaches associated with similar outcomes (treatment retention, positive urine toxicology) compared to treatment as usual. Trials were limited by small samples sizes, lack of reporting harms, and most were conducted prior to the COVID-19 pandemic; observational studies were limited by failure to control for confounding. Conclusions: Limited evidence suggests that telemedicine may enhance access to MOUD with similar effectiveness compared with face-to-face treatment. Few studies have been published since COVID-19, and it is unclear the potential impact of these interventions on the existing racial/ethnic disparities in treatment. The COVID-19 pandemic and need for social distancing led to temporary policy changes for prescribing of MOUD that could inform additional research in this area to support comprehensive policy reforms.